2011
DOI: 10.1186/1752-4458-5-30
|View full text |Cite
|
Sign up to set email alerts
|

Building capacity in mental health interventions in low resource countries: an apprenticeship model for training local providers

Abstract: BackgroundRecent global mental health research suggests that mental health interventions can be adapted for use across cultures and in low resource environments. As evidence for the feasibility and effectiveness of certain specific interventions begins to accumulate, guidelines are needed for how to train, supervise, and ideally sustain mental health treatment delivery by local providers in low- and middle-income countries (LMIC).Model and case presentationsThis paper presents an apprenticeship model for lay c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
215
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 260 publications
(222 citation statements)
references
References 34 publications
4
215
0
3
Order By: Relevance
“…A systematic review of 29 studies showed that lay counsellors in the South African context can be effective if they are appropriately trained and supervised (Peterson et al, 2014). This is confirmed in recent literature (Dewing et al, 2015;Kabamba, 2009;Murray et al, 2011;Peltzer et al, 2009).…”
Section: Resultssupporting
confidence: 79%
“…A systematic review of 29 studies showed that lay counsellors in the South African context can be effective if they are appropriately trained and supervised (Peterson et al, 2014). This is confirmed in recent literature (Dewing et al, 2015;Kabamba, 2009;Murray et al, 2011;Peltzer et al, 2009).…”
Section: Resultssupporting
confidence: 79%
“…Twenty adult counselors (11 from the sites and 12 external) were trained in TF-CBT via the apprenticeship model: a 10-day on-site training of counselors and supervisors, followed by weekly meetings of local supervisors with groups of counselors and weekly supervisor consultation with TF-CBT experts. 18 suggests broad applicability across a wide range of trauma types and acceptability among ethnically diverse therapists, children, and parents. 24 We previously modified TF-CBT for Zambia 13 and documented its feasibility in an open trial.…”
Section: Interventionmentioning
confidence: 98%
“…It consisted of five face-to-face sessions, with a key feature of being affordable in most settings, because it can be offered not only by specialists but also by supervised non-specialists with no prior training or experience in mental health care delivery. We used an apprenticeship (on-the-job learning) model for training and supervising the non-specialists 5 , which involved an initial 6-day training programme by a master trainer to local mental health specialists, who in turn provided an 8-day training programme to six nonspecialists. Training of both supervisors and non-specialists was followed by four weeks of practice under supervision of the local trainers.…”
Section: Problem Management Plus (Pm1): Pilot Trial Of a Who Transdiamentioning
confidence: 99%